2015
DOI: 10.2105/ajph.2014.302112
|View full text |Cite
|
Sign up to set email alerts
|

The Alcohol Policy Environment and Policy Subgroups as Predictors of Binge Drinking Measures Among US Adults

Abstract: A small number of policies that raised alcohol prices and reduced its availability appeared to affect binge drinking.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
61
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 75 publications
(66 citation statements)
references
References 27 publications
4
61
0
1
Order By: Relevance
“…When investigating the associations between the alcohol policy environment and the prevalence of binge drinking in US states, a recent publication found that the most promising policies to reduce binge drinking, in addition to increasing the price of alcoholic beverages, were those which targeted the general population (as opposed to policies focusing on underage drinkers), focused on alcohol consumption (e.g. policies focusing on the production, sale or use of alcohol rather on impaired driving), and reduced the availability of alcohol (Xuan et al, 2015). In sum, an effective political strategy to reduce binge drinking at the population level should contain both price increases and efforts to reduce alcohol availability.…”
Section: Structural Interventions: Policy and Environmental Factorsmentioning
confidence: 99%
“…When investigating the associations between the alcohol policy environment and the prevalence of binge drinking in US states, a recent publication found that the most promising policies to reduce binge drinking, in addition to increasing the price of alcoholic beverages, were those which targeted the general population (as opposed to policies focusing on underage drinkers), focused on alcohol consumption (e.g. policies focusing on the production, sale or use of alcohol rather on impaired driving), and reduced the availability of alcohol (Xuan et al, 2015). In sum, an effective political strategy to reduce binge drinking at the population level should contain both price increases and efforts to reduce alcohol availability.…”
Section: Structural Interventions: Policy and Environmental Factorsmentioning
confidence: 99%
“…5 The effect magnitude of the APS for reducing the odds of youth binge drinking was similar to that for reducing the odds of adult binge drinking. 29 For youth drinking measures, however, APS score calculation methods that incorporated policy efficacy ratings (in addition to implementation ratings) did not improve goodness of fit, whereas incorporating both efficacy and implementation ratings improved goodness of fit to predict adult binge drinking. 31 One possible explanation is that panelists' policy efficacy ratings for adults had greater construct validity than their efficacy ratings for youth.…”
Section: Adult Consumption As Mediator Of Population-oriented Policiementioning
confidence: 94%
“…Alcohol Policy Scale (APS) scores, with higher scores representing stronger mixes of alcohol policies, demonstrate good construct validity to predict lower odds of binge drinking and alcoholimpaired driving among adults. 29,31,32 To date, no study has assessed the relationship between the alcohol policy environment and youth drinking in the United States, nor the independent relationships between population-oriented versus youthoriented policies and youth drinking. As shown in Fig 1, the objectives of this study were to assess the relationship of the alcohol policy environments with youth drinking and youth binge drinking, determine the independent relationships between population-oriented policies and youth-oriented policies and youth drinking behaviors, and examine whether adult drinking mediates the relationship between population-oriented policies and youth drinking.…”
Section: Articlementioning
confidence: 99%
See 2 more Smart Citations